2007
DOI: 10.1016/j.yqres.2006.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Lacustrine evidence for moisture changes in the Nebraska Sand Hills during Marine Isotope Stage 3

Abstract: In the central Great Plains of North America, loess stratigraphy suggests that climate during the late Pleistocene was cold and dry. However, this record is discontinuous, and there are few other records of late-Pleistocene conditions. Cobb Basin, located on the northern edge of the Nebraska Sand Hills, contains lacustrine sediments deposited during Marine Isotope Stage 3, beginning approximately 45,000 cal yr BP and continuing for at least 10,000 yr. The lake was formed by a dune dam blockage on the ancient N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Playa lakes are useful repositories for paleoclimatic records because geochemical signatures are recorded in allogenic (aeolian) and authigenic (lacustrine) sediments. The hydrological regime and salinity may indicate variations of precipitation and evaporation in response to climatic conditions (Schütt, 2000;Sinha and Smykatz-Kloss, 2003;Jacobs et al, 2007;Wasylikowa et al, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Playa lakes are useful repositories for paleoclimatic records because geochemical signatures are recorded in allogenic (aeolian) and authigenic (lacustrine) sediments. The hydrological regime and salinity may indicate variations of precipitation and evaporation in response to climatic conditions (Schütt, 2000;Sinha and Smykatz-Kloss, 2003;Jacobs et al, 2007;Wasylikowa et al, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…28 ka (Fredlund, 1995). Jacobs et al (2007) document a similar record from the Cobb Basin in the Nebraska Sand Hills. Age control indicates that a lake was present in the Cobb basin at ca.…”
Section: Regional Comparisons Mis 3: Ca 57-28 Kamentioning
confidence: 74%
“…The clay and sedimentological records from the Orca Basin were compared with previously published paleo-environmental records including the Mississippi River discharge intensity (Hill, 2006) and lower Mississippi terrace levels (Rittenour et al, 2005), loess and paleosoil deposition (Forman et al, 1992;Johnson et al, 2007;Wang et al, 2009;Pierce et al, 2011), lacustrine records (Jacobs et al, 2007;Wood et al, 2010), braided vs. meandering river systems in the Atlantic coastal plains (Leigh et al, 2004), pollen association and vegetation (Fredlund, 1995;Baker et al, 2009;Pierce et al, 2011) and summer precipitation over Florida (Grimm et al, 2006;Donders et al, 2011). When we compare data from different cores recovered in the Gulf of Mexico and various continental archives, however, it is important to keep in mind that all records have independent age models which all contain uncertainties.…”
Section: Discussion: Glacial Activity Of the Lis And Moisture Transfers From The Gom During Mis3mentioning
confidence: 99%
“…In the Gulf of Mexico (GOM), climatic conditions depend on the respective positions of the Inter-Tropical Convergence Zone, Jet-Stream, Bermuda High and subtropical gyre (Forman et al, 1995;Liu and Fearn, 2000;Harrison et al, 2003;Knox, 2003). Grimm et al (2006) suggested that climatic conditions over Florida were warm and wet during the coldest periods of Bond cycles, while cold and dry conditions were predominant in interior North America (Wang et al, 2003;Jacobs et al, 2007;Jiménez-Moreno et al, 2010). The conclusions of Grimm et al (2006) are consistent with the hypothesis that decreased North Atlantic Deep Water formation, caused by the calving of icebergs into the North Atlantic during Heinrich events (Ganopolski and Rahmstorf, 2001), reduced the transport of heat from the GOM to northern high latitudes, leading to the warming of Florida.…”
Section: Introductionmentioning
confidence: 99%